Total Endoscopic Thyroidectomy with Intraoperative Laryngeal Nerve Monitoring - Bin Lv; Bin Zhang; Qing-Dong Zeng (International Journal of Endocrinology)
Objective. To evaluate the clinical efficacy of laryngeal nerve (LN) monitoring (LNM) during total endoscopic thyroidectomy via breast approach, with emphasis on the identification rates for RLN and EBSLN and the incidence of RLN paralysis. Materials and Methods. This retrospective study included 280 patients who underwent endoscopic thyroidectomy with or without LNM. RLN and EBSLN were identified using endoscopic magnification in the control group, while they were localized additionally by LNM in the LNM group. Demographic parameters and surgical outcomes were analyzed by statistical methods. Patients in the control group were also stratified by the side of thyroidectomy to determine difference in left and right RLN injury rates. Results. All procedures were successfully conducted without permanent LN damage. The identification rates for RLN and EBSLN were high in the LNM group compared to those of the control group, and the risk difference (RD) of temporary RLN injury between two groups was 6.3%. The risk of damage was slightly higher for the left RLN than for the right RLN in the control group, which was performed by a right-hand surgeon. Conclusion. The joint application of LNM and endoscopic magnified view endows total endoscopic thyroidectomy with ease, safety, and efficiency.